INTERACTIVE METHODS FOR TEACHING ENGLISH IN SECONDARY SCHOOLS (Scientific Conference on Multidisciplinary Studies, 2025)
The effective teaching of English as a foreign language in secondary schools requires innovative and interactive methods that actively engage students in the learning process. This article explores various interactive teaching methodologies, highlighting their impact on student motivation, participation, and language proficiency. The findings demonstrate that interactive methods enhance both the quality of education and the overall student experience, making English learning more effective and enjoyable.